Pengaruh destination image terhadap revisit intention dan intention to recommend melalui satisfaction sebagai variabel intervening - Dian Citaningtyas Ari Kadi; Hari Purwanto; Brilianne Rose Vonseica (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
The purpose of this study was to determine the effect of destination image on revisit intention and intention to recommend through satisfaction as an intervening variable. The research used is quantitative research with a sample of 269 respondents. Using a 5-point Likert Scale and Path Analysis was used for analysis and hypothesis testing. The findings of this study indicate that destination image has an effect on revisit intention, intention to recommend, and satisfaction. While other findings, satisfaction acts as a mediation of the relationship between destination image to revisit intention and intention to recommend. For further research, it is possible to enter the tourist attraction variable.